ANALISIS PELAKSANAAN PENGADUAN MASYARAKAT DI KANTOR SAMSAT KOTA SAMARINDA - Bambang Irawan (Jurnal Administrative Reform, 2017)
This research aims to describe and analyze the mechanism of costumer complaining service in SAMSAT Samarinda as well as identify hindering factors of the mechanism. The results shows that complaining mechanism both direct and indirect in SAMSAT Samarinda was not implemented very optimal. The response process of the complains was also not optimal even when there is a clear SOP. SAMSAT Samarinda already have the infrastruture to collect the complains but not yet used advanced technology to support the costumer who have their complains.